Analisis Emisi dari Pembakaran Bahan Bakar Gas dengan Pendekatan Perhitungan Stoikiometrik - I Made Indradjaja M. Brunner; Hernani Yulinawati (Jurnal Serambi Engineering, 2024)
This article explains the analysis of potential emissions from the combustion of gaseous fuels, namely natural gas, coke oven gas (COG) and blast furnace gas (BFG). Fossil gas fuels are widely used in industrial activities, particularly in the integrated iron and steel industry. Natural gas is generally derived from natural sources and contains mainly methane gas in addition to longer chain hydrocarbon gases and other non-hydrocarbon gas compounds. COG is a by-product of the production of coke from coal and generally contains hydrogen and methane gas. BFG is the flue gas from the process of smelting iron ore in a furnace and consists of a mixture of nitrogen, carbon monoxide, carbon dioxide and hydrogen gas. Theoretical analysis shows that for an energy level equivalent to natural gas, approximately 2.35 times more COG and 11.56 times more BFG are required than natural gas. COG emissions tend to be lower in CO2 but higher in NO2 and SO2 than natural gas emissions. CO2 and NO2 gas emissions from COG are lower than those from BFG. However, CO2 and NO2 gas emissions from BFG are much higher than those from natural gas.